Clinical findings and genetic analysis of the patients with IL-12Rβ1 deficiency from southeast Turkey - Doğruel, Dilek; Gündeşlioğlu, Özlem Özgür; Yılmaz, Mustafa; Alabaz, Derya; Altıntaş, Derya Ufuk; Kocabaş, Emine (The Turkish Journal of Pediatrics, 2019)
IL-12Rβ1 deficiency is an autosomal recessive disorder characterized by predisposition to poorly pathogenic mycobacteria, salmonella and candida species. We aimed to analyze the clinical manifestations, immunological and genetic features of IL-12Rβ1 deficiency in 10 Turkish patients from a single center. We retrospectively studied the clinical manifestations and genetic analysis of the IL-12Rβ1 deficiency patients from 2008 to 2016. Ten patients were diagnosed and followed for eight years. The mean age at onset and diagnosis were 24.1±42.5 (med:10.5) and 52.3±6.83 (med:20) months, respectively. Parental consanguinity rate was 81.8%. All patients were BCG vaccinated. Abscess and axillary lymphadenopathy in the vaccinated area was the most common initial presentation following the BCG vaccination, six patients had recurring oral candidiasis. Active infections were treated appropriately, in addition to prophylactic therapy with IFNɣ. We identified 6 different mutations in the IL12RB1 gene in 10 patients including 5 splice-site mutations, 3 missense, 1 frameshift, 1 premature stop codon. One of these mutations was novel. The most common mutation was IVS8+1G > A(c.783+1G > A) followed by p.R175W(c.523C > T). This study emphasizes that patients presented with abscess and axillary lymphadenopathy associated with BCG vaccination should be evaluated for IL-12Rβ1 deficiency.